THE EFFECT OF USING COLLABORATIVE STRATEGIC READING (CSR) ON STUDENTS’ ACHIEVEMENT IN READING COMPREHENSION ON HORTATORY EXPOSITION TEXT - Rut Emi Febriyani Simamora; Lince Sihombing; Johannes Jefria Gultom (Universitas Negeri Medan, 2015)
This study is aimed at finding out the effect of Collaborative Strategic Reading (CSR) on students’ achievement in reading comprehension on hortatory exposition text. Experimental design was applied in this research. The population was the 2014/2015 second year students (grade XI) of SMA Swasta YAPIM Medan. There were two paralel classes that consisted of 34 students. The total number of the population were 68 students. The total number of the sample were 68 students. The researcher selected the sample by using total sampling technique. The sample was divided into two groups, experimental group and control group. The experimental group was taught by using Collaborative Strategic Reading (CSR) strategy while the control group was taught without using Collaborative Strategic Reading (CSR) strategy. The data were taken by administering the pre-test and post-test to both control and experimental groups. These data were analyzed by using t-test. The result of computing the t-test obviously showed that t-observed (5.61) is higher than t-table (1.99) with the degree of freedom (df= 66) at the level significance 0.05. It means that the alternative hypothesis stating that there is a significant effect of Collaborative Strategic Reading (CSR) on students’ achievement in reading comprehension on hortatory exposition text is accepted. Keywords : Collaborative Strategic Reading, Reading Comprehension